AGC optimization of supercritical heating unit. (October 2020) - Liu, Enren; Yan, Qing; Li, Yanyan; Shi, Shuo; Li, Jun; Gao, Song; Yu, Qingbin
Abstract: A 330MW supercritical coal-fired unit, the unit undertakes the task of industrial steam supply all year round, with a rated steam supply flow of 250t/h. Due to the poor heat storage capacity of the unit and the large industrial steam supply of the unit, the unit is not performing well in the AGC-PROPR mode, Periodic large fluctuations in main steam pressure affect the safety of the unit, AGC performance indicators do not meet the requirements, and this unit is often evaluated by the power grid. In order to improve the AGC adjustment performance of the unit, increase the conversion circuit of heating load and electric load, improve the logic of steam turbine main control, boiler main control and fuel main control, and optimize the PID parameters in a targeted manner. Through optimization, the main steam pressure of the unit does not fluctuate greatly, and the K1, K2, K3 indicators meet the requirements.